2017
DOI: 10.1016/j.micromeso.2016.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pb(II) ion-imprinted materials based on bis-pyrazolyl functionalized mesoporous silica for the selective removal of Pb(II) in water samples

Abstract: Three highly efficient adsorbents Pb-IIMS-SBA-15, Pb-IIMS-MCM-41 and Pb-IIMS-FDU-12 for Pb(II) were prepared by grafting the functional monomer 4-(di (1H-pyrazol-1-yl) methyl) phenol (DPP) on corresponding mesoporous silicas with Pb(II) as temple. All these three Pb(II) ion-imprinted mesoporous silica (Pb-IIMS) were characterized by Fourier transform-infrared spectroscopy (FT-IR), solid-state 29 Si and 13 C NMR spectra, scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…The shape of the isotherms is similar for the two materials; they can be roughly assimilated to type IV isotherm. The hysteresis loop, which is materialized by the non-superimposition of adsorption and desorption isotherms, corresponds to type H 2 [ 38 ]; however, the width of the loop is weakly marked compared to other composite silica materials [ 39 ]. H2 loop is usually associated with the so-called ink bottle-neck porous system—this is even more marked for polymer functionalized material due to the particle obstruction of micropores at the surface of raw silica microbeads.…”
Section: Resultsmentioning
confidence: 99%
“…The shape of the isotherms is similar for the two materials; they can be roughly assimilated to type IV isotherm. The hysteresis loop, which is materialized by the non-superimposition of adsorption and desorption isotherms, corresponds to type H 2 [ 38 ]; however, the width of the loop is weakly marked compared to other composite silica materials [ 39 ]. H2 loop is usually associated with the so-called ink bottle-neck porous system—this is even more marked for polymer functionalized material due to the particle obstruction of micropores at the surface of raw silica microbeads.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, several studies reported surface functionalization of mesoporous silica materials such as SBA-15, MCM-41, and KCC-1 with various organic groups [ 1 , 2 , 21 , 23 , 33 , 34 ]. In comparison, there are few reports regarding the functionalization of mesoporous silica FDU-12 [ 35 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of a large number of hydroxyl groups on the surface of mesoporous silica materials, surface functionalization with a variety of organic moieties seems to be relatively easy 47 . In this case, there are few reports regarding the functionalization of mesoporous silica FDU-12 48 52 .…”
Section: Introductionmentioning
confidence: 99%